2014
DOI: 10.5194/acp-14-10687-2014
|View full text |Cite
|
Sign up to set email alerts
|

Do anthropogenic, continental or coastal aerosol sources impact on a marine aerosol signature at Mace Head?

Abstract: Abstract. Atmospheric aerosols have been sampled and characterised at the Mace Head north-east (NE) Atlantic atmospheric research station since 1958, with many interesting phenomena being discovered. However, with the range of new discoveries and scientific advances, there has been a range of concomitant criticisms challenging the representativeness of aerosol sampled at the station compared to that of aerosol over the pristine open-ocean. Two recurring criticisms relate to the lack of representativeness due t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
59
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 59 publications
(88 reference statements)
5
59
0
Order By: Relevance
“…environments had a range of approximately three orders of magnitude (~10 1 − 10 cm -3 ). In most cases, the CN 2.5 and CN 10 concentrations were less than ~2000 cm -3 , with averages of 505 ± 280 and ± 264 cm -3 , respectively, which were in agreement with those reported in previous studies conducted at other Arctic stations (Asmi et al, 2016;Burkart et al, 2017;Freud et al, 2017) and remote marine regions (O'Dowd et al, 2014;Sellegri et al, 2006;Jang et al, 2019;Yum et al, 1998;Hudson and Yum, 2002). For example, four years of observational data from the Arctic Climate Observatory in Tiksi, Russia, showed that the monthly median CN concentration ranged from ~184 cm -3 in November to ~724 cm -3 in July (Asmi et al, 2016).…”
Section: Overall Particle Number Concentrationssupporting
confidence: 91%
“…environments had a range of approximately three orders of magnitude (~10 1 − 10 cm -3 ). In most cases, the CN 2.5 and CN 10 concentrations were less than ~2000 cm -3 , with averages of 505 ± 280 and ± 264 cm -3 , respectively, which were in agreement with those reported in previous studies conducted at other Arctic stations (Asmi et al, 2016;Burkart et al, 2017;Freud et al, 2017) and remote marine regions (O'Dowd et al, 2014;Sellegri et al, 2006;Jang et al, 2019;Yum et al, 1998;Hudson and Yum, 2002). For example, four years of observational data from the Arctic Climate Observatory in Tiksi, Russia, showed that the monthly median CN concentration ranged from ~184 cm -3 in November to ~724 cm -3 in July (Asmi et al, 2016).…”
Section: Overall Particle Number Concentrationssupporting
confidence: 91%
“…7) on the other hand, were lower than the measured equivalent black carbon (EBC) in general but followed the temporal variation very well. In a study about the aerosols at Mace Head, O'Dowd et al (2014) reported that EBC measurements can significantly overestimate black carbon concentration by up to 50% or more. Overestimation of SIA could result from either too high precursor emissions or too much particle formation in the aqueous phase.…”
Section: Inorganic Aerosolsmentioning
confidence: 99%
“…On the other hand, sea surface water is also a reservoir of organic matter that can be injected into the air and enriched in the particles (Aller et al, 2005;Kuznetsova et al, 2005;Schmitt-Kopplin et al, 2012;. Organic matter has been observed to dominate the particle mass (up to 77 %) during phytoplankton bloom periods at a coastal station in Ireland (O'Dowd et al, 2004;Ovadnevaite et al, 2011). However, many marine aerosol studies were based on observations of islands or in coastal areas, where biological activities are much higher than the remote ocean (as illustrated by global maps of chlorophyll a -Chl a: https://earthobservatory.nasa.gov/GlobalMaps/view.…”
Section: Introductionmentioning
confidence: 99%
“…Significant impacts from ship and continental emissions were observed over the Pacific and Atlantic (63 % of the sampling time; Frossard et al, 2014), the Arctic (Chang et al, 2011), and the North Pa-cific between southern Asia and northern Japan (Choi et al, 2017). Nevertheless, there are still some regions with little anthropogenic impact on marine aerosols, such as the station on the coast of Ireland in the northeastern Atlantic (Ceburnis et al, 2011;O'Dowd et al, 2014). Due to the paucity of ship-based measurements, the non-marine influence on MBL aerosol particles is still unknown, especially for a large area of the oceans.…”
Section: Introductionmentioning
confidence: 99%